PS8:154 Therapeutic and cardiovascular disease burden in undifferentiated connective tissue disease and systemic lupus erythematosus: results from the lupus extended autoimmune phenotype study (leap) cohort. (21st March 2018) - Dyball, S; Reynolds, J; Bruce, IN; Parker, B
Abstract : Purpose: Connective tissue diseases (CTDs) are heterogeneous with overlapping clinical features and shared immunopathology. We sought to assess clinical characteristics, arterial stiffness and therapeutic exposures in a mixed CTD cohort using both clinician diagnosis and classification criteria. We specifically compared these factors in undifferentiated CTD (UCTD) and systemic lupus erythematosus (SLE). Method: Data was collected prospectively in 181 CTD patients in Lupus Extended Autoimmune Phenotype Study (LEAP) between May-2014 and June-2017. Patients were initially grouped according to clinician diagnosis. Patients with a clinician diagnosis of UCTD were reviewed and reclassified, where appropriate, using ACR-1982/1997 SLE, ACR/EULAR-2016 Sjögren's syndrome, ACR/EULAR-2013 Systemic Sclerosis, and 1975-Myositis criteria. Arterial stiffness (pulse wave velocity-PWV) was measured using the TensioMed device (TensoMed-LTD, Budapest). PWV between groups was analysed by linear regression, and adjusted for confounders (age, gender, ethnicity, smoking, systolic blood pressure and disease duration). Results: Baseline characteristics are described in Table-1. UCTD patients had comparatively shorter disease duration than many CTDs but significant treatment burden with 15 (33%) taking an immunosuppressant and 20 (44%) taking oral-steroids. UCTD patients had no renal disease and lower serositis compared to the SLE cohort. As expected, pulmonary artery hypertension and interstitial lung disease were comparatively lower in UCTD. Using classification criteria, 15 UCTD patients could be reclassified as SLE and 1 as Sjögren's syndrome; relating predominately to musculoskeletal and cutaneous features including ulcers-(30.6%), photosensitive rash-(40.8%) and arthritis-(55.1%) rather than deep-organ manifestations. There was higher immunosuppressant-use in reclassified UCTD patients (62% vs 39%, p=0.013) suggesting they required more aggressive intervention. The UCTD and SLE cohorts were of similar ages and had comparable PWV (7.65 vs 7.45 m/s, p=0.746), with no significant differences even when UCTD patients were reclassified. A historic control group of 19 healthy subjects aged 30.7 years (25.0, 32.9) had a PWV of 6.20 m/s suggesting UCTD patients have increased cardiovascular burden, similar to SLE. Conclusions: Patients diagnosed with UCTD may meet classification criteria for other CTDs and it is important to continuously reassess these patients for new or evolving features. UCTD patients are also often exposed to significant therapies, including immunosuppressants. There is similar arterial stiffness to the SLE cohort suggesting a comparatively high cardiovascular burden.